Association Of Triple Negative Breast Cancer (TNBC) With BRCA-1 Mutation And Ethnicity - Permana, Km. Allan Wahyu; Permana, M. Agung Yudistira; Nisa, Sayyidatun; Sukohar, Asep (Medula, 2019)
Breast cancer is the most common cancer suffered by women in the world, 15-20% is a subtype of triple negative breast cancer (TNBC). TNBC is a subtype of breast cancer that does not express genes for estrogen receptors (ER), progesterone receptors (PR) and HER2 overexpression, which is clinically more aggressive and unresponsive to standard therapy, thus it can worsen the prognosis. It suggests that TNBC is associated with BRCA-1 gene mutation, moreover in African-Americans. So this study aims to determine the association of TNBC with BRCA-1 gene mutation and ethnicity. International journal literature review. BRCA-1 gene mutations increased 45%-85% of the risk of breast cancer growth and 15% -25% of TNBC have BRCA-1 gene mutations which resulted in activation inefficiencies of the HR DNA repair pathway. TNBC occurred in 60% of the black race, disproportionate incidence of TNBC greater in African ethnicity compared to other ethnic groups in the world and has the worst prognosis among all races. There is asignificant association between TNBC with BRCA-1 gene mutations and ethnicity especially in African-Americans.